The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.3389/fpls.2013.00354
|View full text |Cite
|
Sign up to set email alerts
|

Root Apex Transition Zone As Oscillatory Zone

Abstract: Root apex of higher plants shows very high sensitivity to environmental stimuli. The root cap acts as the most prominent plant sensory organ; sensing diverse physical parameters such as gravity, light, humidity, oxygen, and critical inorganic nutrients. However, the motoric responses to these stimuli are accomplished in the elongation region. This spatial discrepancy was solved when we have discovered and characterized the transition zone which is interpolated between the apical meristem and the subapical elon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
140
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(145 citation statements)
references
References 248 publications
(474 reference statements)
1
140
0
Order By: Relevance
“…The position of the PD/TD boundary is particularly difficult to establish because it fluctuates in time within a cell file and, additionally, is frequently different among different files of cells of the same type or different types (Baluska and Mancuso, 2013;Ivanov and Dubrovsky, 2013). Because of this, the PD/ TD boundary can only be approximated with a certain error, which should be estimated (Ivanov and Dubrovsky, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The position of the PD/TD boundary is particularly difficult to establish because it fluctuates in time within a cell file and, additionally, is frequently different among different files of cells of the same type or different types (Baluska and Mancuso, 2013;Ivanov and Dubrovsky, 2013). Because of this, the PD/ TD boundary can only be approximated with a certain error, which should be estimated (Ivanov and Dubrovsky, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the apical part (distal) of this region seems to be characterized mainly by cells that optionally can reenter the cell cycle, whereas cells of the basal (proximal) part of this zone are able to readily enter into the fast cell elongation region. 42,44,45 This developmental feature could be differentially regulated at the opposite root flanks, providing the root apices with an effective mechanism to re-orientate growth in response to environmental stimuli. 44 The transition zone is a unique zone being competent for integration of diverse endogenous and exogenous signals, and translating them into adaptive differential growth responses.…”
Section: The Root Transition Zonementioning
confidence: 99%
“…It has also been demonstrated that plants have complex sensory systems which feed into their adaptive behavior [3739]. Tropisms of plant organs, such as gravitropism and phototropism, are based on cellular-based sensory events that are spatially separated from motoric zones [37,39,40]. Rapid electrical and slower chemical cell-cell communications, accomplished across plant synapses, are inter-linking and integrate sensory-motoric circuits of plant organs.…”
Section: The Cell In the 21st Centurymentioning
confidence: 99%